PINJAMAN DANA DARI TIONGKOK KE SRI LANKA UNTUK PEMBANGUNAN PELABUHAN HAMBANTOTA DI SRI LANKA - Athariq Dwi Awaly; Yusnarida Eka Nizmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The Belt and Road Initiative (BRI) is one of the strategies developed by China under the government of Xi Jinping in 2013. Belt and Road itself is business economy, diplomatic, And geopolitics multifaceted. Objective from held this policy is to link the economies of Eurasia, East Africa, Europe and more than 71 countries. Sri Lanka is one of China's target countries in implementing this strategy. China has carried out various relations in Sri Lanka such as cooperation, investment. Therefore, the researcher drew the question "Why did China lend funds to Sri Lanka for the construction of the Hambantota Port? â€ To answer this question researchers use the theory of foreign debt. This theory is considered appropriate because China is the main actor in cooperating through Chinese loans to Sri Lanka to build the Hambantota port. The research method used in this study is a descriptive qualitative research method. The results of this study indicate that China's interest in lending funds to Sri Lanka is not only for economic cooperation but also for implementing the Belt and Road Initiative policy and acquiring the Hambantota port. By taking advantage of Sri Lanka's inability to repay China's foreign debt, China managed to gain an advantage in the form of the Hambantota port authority. Keywords: Belt and Road Initiative, External Debt, Financial Management